2019
DOI: 10.1021/acsaem.8b02229
|View full text |Cite
|
Sign up to set email alerts
|

Black Silicon Photoanodes Entirely Prepared with Abundant Materials by Low-Cost Wet Methods

Abstract: Supporting Information. Experimental section, XPS survey spectra, supplementary figures, and tables are provided in supporting information. The following files are available free of charge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…The first one is commercially available and the second one was prepared from n‐Si planar by a simple and scalable alkaline treatment (see the Experimental Section for details). Both surfaces exhibit different optical properties and are composed of planar crystalline facets, ensuring a low density of surface defects with respect to other types of structured Si (i.e., black Si or Si nanowires) . As shown by the reflectance spectra of Figure 1 a, light absorption is enhanced on n‐Si mPy in the 300–1050 nm range, which should be beneficial in terms of photoelectrochemical properties provided that the additionally absorbed photons are effectively employed for OER.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is commercially available and the second one was prepared from n‐Si planar by a simple and scalable alkaline treatment (see the Experimental Section for details). Both surfaces exhibit different optical properties and are composed of planar crystalline facets, ensuring a low density of surface defects with respect to other types of structured Si (i.e., black Si or Si nanowires) . As shown by the reflectance spectra of Figure 1 a, light absorption is enhanced on n‐Si mPy in the 300–1050 nm range, which should be beneficial in terms of photoelectrochemical properties provided that the additionally absorbed photons are effectively employed for OER.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports by our group, and others, have demonstrated that aqueous electrodeposition of transition metals nanoparticles (NPs) on n‐Si is effective to prepare inhomogeneous Si/metal Schottky junctions that can be further employed as stable Si‐based photoanodes without protection layer. This type of photoanode has been reported, so far, for n‐Si/Ni and n‐Si/Co junctions and it has been recently shown that the performance of these systems can be enhanced by using an additional catalytic shell, typically a hydroxide, or a metallic coating, over the NPs. To the best of our knowledge, this phenomenon has never been applied to n‐Si/Fe junctions so far, which we present for the first time in this article.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers sequentially deposited titanium dioxide films, platinum nanoparticles, and titanium dioxide films on the surface to achieve the protection of strong acids and strong bases. In 2019, researchers [ 86 ] fabricated the black silicon by combining with photochemical and chemical etching methods. After the formation of NiNPs and SiO x on the material surface, NiFe was deposited to make a photoanode without a protective layer.…”
Section: Applicationsmentioning
confidence: 99%
“…Black silicon has excellent absorption and low reflectance in the NIR band. Since the late 1990s, when Eric Mazur, a professor at Harvard University, discovered black silicon by accident [ 9 ], researchers have been exploring its application to infrared photodetection [ 47 , 63 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ] and ultrahigh sensitivity in the ultraviolet band and visible light range [ 90 , 91 , 92 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Significant improvement in the durability of Black-Si photocathodes in both acid and alkaline medium was demonstrated. Contrary to these results, Oh et al, (2019) [11] reported that transition metal NPs electrodeposited directly on n-type Black-Si surface can stabilize photoanodes without the need for a protection layer. However, the role of protective layer in their study was, in fact, played by thermally grown SiO x .…”
Section: Introductionmentioning
confidence: 89%